Low back pain during pregnancy and Kinesio tape application - (:unkn) unknown (IOS PRESS, 2017)
BACKGROUND AND OBJECTIVE: Low back pain is a common problem during pregnancy. Although the pain usually occurs in the third trimester, it might be seen in the first trimester, too. There are various types of applications for the treatment of low back pain during pregnancy. However, there is a lack of evidence for the effectiveness of each method. If there is not an obvious deficit, bed rest, exercise, conventional physiotherapy, using protective principles for the lumbar area are recommended, since the main and the only complaint is low back pain. It is aimed in the current review to investigate the use of Kinesio tape in the low back pain seen during pregnancy and to review the literature related to this subject. CONCLUSION: There are only a few studies investigating the effect of Kinesio tape during pregnancy in the literature and they mostly did not aim to study the low back pain, further evidence and studies are needed to investigate the use of Kinesio tape for the low back pain seen during pregnancy as there is not evidence strong enough. Kinesiotape application aims to increase circulation and mobility, and regarding these gains decreased pain and increased performance are expected.
Keywords: Kinesiotape; low back pain; physiotherapy; pregnancy; PELVIC GIRDLE PAIN; ACUPUNCTURE